SRESS AND FATIGUE LIFE OF PITTING DEFECTS ON PUMPING UNIT GEAR - BAI YunSong; MUTELLIP AhMat; BAI HaoYu; CHEN Zhi (Jixie qiangdu)
Rack-pinion pumping unit is widely used in Xinjiang oilfields. In order to analyze the pitting damage and fatigue life of gear in rack-and-pinion pumping unit, Firstly, the model of rack-and-pinion was established, the elements of tooth surface and root were extracted for static strength analysis, and then compared with contact theory; Secondly, Pitting defects of different sizes were established by elements editing, and the influence of pitting growth on contact stress was analyzed; Finally, fatigue life under different pitting effects was calculated based on linear fatigue damage theory. The results show that with the growth of pitting defects, the contact stress increases and the fatigue life decreases; The pinion interference occurs in the transition section, the stress concentration is worst, and the fatigue life is low, the overall fatigue damage starts from the tooth top; The pitting extend along the tooth profile direction mainly affects the duration of stress concentration, and along the tooth width mainly affects the amplitude of stress change.